Respons Pemberian dan Penetapan Status Hara Si pada Tanaman Padi - Mirawanty Amin; Budi Nugroho; . Suwarno; Dyah Tjahyandari Suryaningtyas (Institut Pertanian Bogor, 2019)
The use of silica fertilizer still has been included in cultivation technology: however, nutrient status for paddy soil is rarely reported in Indonesia. It is necessary to carry out a research on the determination of nutrient status and the influence of silica fertilizer on rice production. The aims of this research are to investigate the effect trass on soil chemical properties, discover of silica fertilizer on rice production and determine the nutrient status of Si by Cate Nelson and Contiunous Curves. The results showed that the effect of trass has a significant on soil chemical properties such as pH H2O and available Si. The nutrient status of Si was estimated by using several different extractants namely H2O; CaCl2; Ammonium Acetate pH 4.8; and Acetate Buffer pH 4 gives a critical limit value of 13, 17, 34, and 37 mg kg-1, equivalent to 28 mg kg-1, 36 mg kg-1, 73 mg kg-1, and 79 mg kg-1 SiO2, respectively. Meanwhile, the Si availability in the medium class based on Continuous Curves Method extracted by H2O; 0.01 M CaCl2; NH4OAc pH 4.8; and Na-acetate pH 4 were 18-34, 33-41, 44-79, and 42-81 mg SiO2 kg-1, espectively. Burned trass with dose of 10 g kg-1 gives the highest rice production of 44.19 g pot-1 equivalent to 7.07 ton ha-1.